The Strength Properties Of Adhesive Joints Used In The Creation Of Plastic Model Kits Evaluation - M. I. Kalinichenko; B. M. Nemenenok (Литьë и металлургия)
The article presents information on model plastics presented on the market of the Republic of Belarus. The analysis of methods for creating accurate model sets using both 3D printing from thread and granules, and obtaining model sets from an array of model plastic using 3D milling is carried out. The properties were evaluated and the behavior of glued and solid plastics under compressive loads in the longitudinal and transverse directions was shown. Economic efficiency assessment of various methods of obtaining model sets is given, based on a comparison of the cost of materials and the production process itself.